iTRAQ-Based Proteomic Profile Analysis of the Hepatopancreas of Caribbean Spiny Lobsters Infected With Panulirus argus Virus 1: Metabolic and Physiological Implications - Zamora-Briseño, Jesús Alejandro; Ruiz-May, Eliel; Elizalde-Contreras, José Miguel; Hernández-Velázquez, Ioreni Margarita; Hernández-Pérez, Ariadne; Fuentes-García, Ana Guadalupe; Herrera-Salvatierra, Nancy; Briones-Fourzán, Patricia; Pascual-Jiménez, Cristina; Lozano-Álvarez, Enrique; Rodríguez-Canul, Rossanna (Frontiers in Microbiology, 2020)
The Caribbean spiny lobster Panulirus argus (Latreille, 1084) sustains economically valuable fisheries throughout the wider Caribbean region. This species is currently affected by the pathogenic virus Panulirus argus Virus 1 (PaV1) that causes a systemic and chronic-degenerative infection in juvenile spiny lobsters P. argus. To date, there is no available information regarding the host alterations induced by this pathogen at the molecular level. In the present study, comparative proteomic analyses of the changes in the hepatopancreas between infected and non-infected juvenile lobsters were analyzed by isobaric tags for relative and absolute quantitation (iTRAQ) coupled to synchronous precursor selection (SPS)-based MS3. We identified a total of 636 proteins, being 68 down-regulated and 71 up-regulated proteins. Among the down-regulated proteins, we identified several enzymes involved in the metabolism of hormones and lipids, digestive proteases and glycosidases, while proteins associated with the histone core, protein synthesis, immune response and RNA regulation were up-regulated. Several misregulated enzymes involved in the regulation of neuromodulators were also identified. RT-qPCR assays were used to validate the expression of transcripts encoding for selected differential proteins that were in concordance to proteomic data, as well as the tendency observed in the enzymatic activities of trypsin, chymotrypsin, and glycosidase. In a similar way, we observed glycogen reduction in muscle, and an increase in plasma acylglycerides and glucose, which may be explained by proteomic data. This study provides the first insight into the molecular changes in the hepatopancreas of Caribbean spiny lobsters associated to PaV1 infection Data provided herein would help to clarify the origin of the molecular misregulations observed at macroscopic level in this host-pathogen interaction.